Pharmacokinetic evaluation and safety of topical 1% morphine sulfate application on the healthy equine eye. (19th January 2018) - Gordon, Emma; Stang, Bernadette V.; Heidel, Jerry; Poulsen, Keith P.; Cebra, Christopher K.; Schlipf, John W.
Abstract: Objective: To determine if corneal epithelial cell integrity is detrimentally affected by short‐term administration of 1.0% morphine sulfate. Additionally, we sought to determine if topical 1.0% morphine applied to the equine cornea would result in ocular or systemic absorption. Animal studied: Six healthy horses. Procedure: Morphine sulfate (1.0%) was applied topically to one eye every four hours for 72 h before horses were euthanized. Serum samples were collected at varying time points during the study and aqueous and vitreous humor were collected immediately after euthanasia. Morphine quantification in serum, aqueous, and vitreous humor was performed by ELISA. Treated and control corneas were submitted for histopathology. Horses were monitored for adverse ocular and systemic effects throughout the study period. Results: All horses developed mild mucoid ocular discharge in the treated eye. One horse developed a fever during treatment. Morphine was detected in the aqueous humor of the treated eye for all horses with mean ± standard deviation of 165.18 ng/mL ± 87.69 ng/mL. Morphine was detected in vitreous humor of the treated eye of 5 of 6 horses with mean ± standard deviation of 4.87 ± 4.46 ng/mL. Morphine was detected in the serum of 5 of 6 horses at varying time points. Maximum systemic concentration reached in a single horse was 6.98 ng/mL. Corneal histopathology revealed no difference in microscopic appearance between morphine‐treated and control corneas. Conclusions: Topical administration of 1.0% morphine sulfate did not appear to cause any significant ocular or systemic adverse effects. Topical ophthalmic morphine application resulted in both ocular and systemic absorption.